ID180: Metagenomic analysis of Kelantan river post-flood for pathogenic and nonpathogenic microbial identification - Suganthi Appalasamy; Fikri Shamsudin; Jayaraj V.K (2016)
The overflow of Kelantan River during 2014 flood to residential areas and backflow of these water from the residential area and agricultural lands triggered immediate study to identify contaminating pathogenic microbes in the Kelantan River. The water microbial concentration must be quantified to determine the pathogenicity posed to human and ecosystem health. The microbial diversity in the Kelantan River along three cities (Kota Bharu, Tanah Merah and Kuala Krai) were determined using metagenomics 16SrRNA analysis. The water samples at these three points along Kelantan River were collected in triplicate at depth of five meter and five meter away from the river bank. The collected water were then used used for microbial DNA isolation and metagenomics sequences with MiSeq sequencing system. The raw reads (1868713 reads at an average of 400 bp) obtained from metagenomics sequencing were analysed for 16SrRNA gene using MG-RAST database for comparison of microbial diversity in each point of Sungai Kelantan. The metagenomics analysis showed absence of human pathogenic microbes such as Enterobacter or coliforms in Kelantan River. Three major groups of microbes that were found in high concentration in Kota Bahru, Tanah Merah and Kuala Krai river points are Armatimonadeceae (34.1%), Limnohabitatan (4.6%), Sporichthyaceae (3.7%) and Verrucomicrobra (3.3%). The water microbial metagenomics library from these three river points also showed that the bacteria belong to a several widespread nonpathogenic freshwater clusters, including clusters of Polynucleobacter, beta-proteo bacteria, Actinobacteria, Acidovorax and Methylophilaceae. There was also a group of bacteria ie Prosthecobacterfound in concentrations of 3% in all the three river points and this bacteria is commonly found in water with high heavy metal concentration. These microbes that were found in the Kelantan River indicated that the river is void of human pathogenic microbes. However, the mitigation process in Kelantan River could be more focused on reducing the chemical pollutants in the river water which could endanger the surrounding soil and livestock that depend on river water.